Profit Malmquist Index and Its Global Form in the Presence of the Negative Data in DEA. (31st August 2014) - Tohidi, Ghasem; Razavyan, Shabnam; Tohidnia, Simin
Abstract : This paper first introduces the allocative and profit efficiency in the presence of the negative data and then presents a new circular index to measure the productivity change of decision making units (DMUs) for the case that the dataset contains the inputs and/or outputs with the negative values in data envelopment analysis (DEA). The proposed index is decomposed into four components in the two stages. The range directional model (RDM) and the proposed efficiencies are used to compute the proposed index and its components. The interpretations of the components are presented. Finally, a numerical example is organized to illustrate the proposed index and its components at three successive periods of time.